Genes Contributing to Porphyromonas gingivalis Fitness in Abscess and Epithelial Cell Colonization Environments - Miller, Daniel P.; Hutcherson, Justin A.; Wang, Yan; Nowakowska, Zuzanna M.; Potempa, Jan; Yoder-Himes, Deborah R.; Scott, David A.; Whiteley, Marvin; Lamont, Richard J. (Frontiers in Cellular and Infection Microbiology, 2017)
P. gingivalis is an important cause of serious periodontal diseases, and is emerging as a pathogen in several systemic conditions including some forms of cancer. Initial colonization by P. gingivalis involves interaction with gingival epithelial cell and the organism can also access host tissues and spread haematogenously. To better understand the mechanisms underlying these properties, we utilized a highly saturated transposon insertion library of P. gingivalis and assessed the fitness of mutants during epithelial cell colonization and survival in a murine abscess model by high-throughput sequencing (Tn-Seq). Transposon insertions in many genes previously suspected as contributing to virulence showed significant fitness defects in both screening assays. A number of genes not previously associated with P. gingivalis virulence were identified as important for fitness. We further examined fitness defects of four such genes by generating defined mutations. Genes encoding a carbamoyl phosphate synthetase, a replication-associated recombination protein, a nitrosative stress responsive HcpR transcription regulator, and RNase Z, a zinc phosphodiesterase, showed a fitness phenotype in epithelial cell colonization and in a competitive abscess infection. This study verifies the importance of several well-characterized putative virulence factors of P. gingivalis and identifies novel fitness determinants of the organism.